2021
DOI: 10.3389/fmicb.2021.709418
|View full text |Cite|
|
Sign up to set email alerts
|

Extended-Spectrum Beta-Lactamase Producing-Escherichia coli Isolated From Irrigation Waters and Produce in Ecuador

Abstract: In cities across the globe, the majority of wastewater – that includes drug resistant and pathogenic bacteria among other contaminants – is released into streams untreated. This water is often subsequently used for irrigation of pastures and produce. This use of wastewater-contaminated streams allows antibiotic-resistant bacteria to potentially cycle back to humans through agricultural products. In this study, we investigated the prevalence of extended-spectrum β-lactamase (ESBL)-producing Escherichia coli iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…Antibacterial activity has been studied mainly for both Gram‐positive and Gram‐negative pathogens associated with the wound, skin, and mucosal infections (Abdel‐Shafi et al., 2022; Diekema et al., 2019; Mejia et al., 2021; Montero et al., 2021), such as Staphylococcus aureus , Pseudomonas aeruginosa , Escherichia coli , and Salmonella enterica subsp. enterica serovar Typhimurium.…”
Section: Resultsmentioning
confidence: 99%
“…Antibacterial activity has been studied mainly for both Gram‐positive and Gram‐negative pathogens associated with the wound, skin, and mucosal infections (Abdel‐Shafi et al., 2022; Diekema et al., 2019; Mejia et al., 2021; Montero et al., 2021), such as Staphylococcus aureus , Pseudomonas aeruginosa , Escherichia coli , and Salmonella enterica subsp. enterica serovar Typhimurium.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies in Ecuador have also found differing prevalence rates, depending on the source. For example, a low prevalence was found in dogs, at 25% ( 11 ), and irrigation water, at 18% ( 13 ), whereas in chickens rates of more than 95% were found ( 12 , 25 ). We do not have a clear explanation for why there are differences, but diet, animal husbandry practices and the environment might play a part.…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, Ortega-Paredes et al reported the first clinical isolate of colistin-resistant E.coli harboring the mcr-1 gene in Ecuador in an adolescent with appendicitis ( 10 ). Since then, studies of animals on rural farms where there is extensive use of colistin as a growth promoter have shown widespread distribution of colistin-resistant E.coli , with a high proportion of isolates containing mcr-1 genes ( 11 13 ). With the growing importance of the One Health concept, documenting the prevalence of colistin-resistance genes in both humans and animals in Ecuador is critical to establish a baseline of how far the mcr genes have dispersed ( 14 ).…”
mentioning
confidence: 99%
“…Z 1-α/2 = Standard normal variant at 5% type I error (P < 0.05); P = Expected prevalence of 4.0-10.12% was based on previous studies [7,21,[28][29][30][31][32][33]; d = Absolute error or precision (which is 5%). The expected minimum sample to be collected ranged from 59-140.…”
Section: Study Area and Sample Collectionmentioning
confidence: 99%